KEAMANAN DAN EFIKASI PEMBERIAN SEL PUNCA MESENKIMAL (MESENCHYMAL STEM CELLS) PADA TERAPI LUKA BAKAR: SYSTEMATIC REVIEW - Theresia Dini (2021)
Burns are a serious problem with high morbidity and mortality rates worldwide and require immediate medical attention. There are various treatment options available, but the treatment that is commonly used does not provide significant results with very long healing times and has limitations in terms of donors and complications. Mesenchymal stem cells (MSCs) have the potential to be used as an alternative therapy for healing burns because it can be isolated from various sources and is ideal for tissue regeneration through its good immunological properties. This systematic review study was conducted to determine the safety and efficacy of administering MSCs to burns and to determine which source of MSCs is the most effective for burn therapy. This research was conducted by reviewing several studies through the PubMed, Google Scholar, Science Direct, and DOAJ online databases using the PRISMA-P 2020 method based on inclusion and exclusion criteria that were re-selected through the JBI Critical Appraisal Tools. The results of research from 13 literatures showed that MSCs were safe for use in burn therapy with minimal side effects/complications and had the potential to repair tissue and accelerate burn healing through several mechanisms. The most effective source of MSCs in burn therapy has not been found. This is because the treatment of MSCs in burns is influenced by donor characteristics related to the severity and area of the burn. Based on this, it can be concluded that the administration of mesenchymal stem cells (MSCs) is safe and effective in burn therapy.